2021
DOI: 10.3390/ijerph18063184
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Biomarkers and Work-Related Stress in Night Shift Workers

Abstract: Work organization, such as shifts and night work, can interfere with the perception of work-related stress and therefore on the development of pathological conditions. Night shift work, particularly, can have a negative impact on workers’ wellbeing by interfering with the biological sphere. The aim of this study is to evaluate the associations between work activities, shift work effects and stress-related responses in 106 dock workers enrolled in southeast Italy. Dock workers’ tasks consist of complex activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…In general, sleep disturbances are likely to be associated with aggressive subtypes of BC, as demonstrated by the Western New York Exposures and Breast Cancer study ( 82 ), conducted on a sample of 1,122 subjects with incident BC. This investigation also showed that sleep quality, well-known to be influenced by occupational features ( 42 ), is also linked to the state of menopause. However, no association was found between BC risk and sleep duration, sleep quality, use of sleep medication, frequency of insomnia and daytime napping in a case-controlled study conducted in China ( 65 ).…”
Section: Mechanistic Pathwayssupporting
confidence: 62%
See 1 more Smart Citation
“…In general, sleep disturbances are likely to be associated with aggressive subtypes of BC, as demonstrated by the Western New York Exposures and Breast Cancer study ( 82 ), conducted on a sample of 1,122 subjects with incident BC. This investigation also showed that sleep quality, well-known to be influenced by occupational features ( 42 ), is also linked to the state of menopause. However, no association was found between BC risk and sleep duration, sleep quality, use of sleep medication, frequency of insomnia and daytime napping in a case-controlled study conducted in China ( 65 ).…”
Section: Mechanistic Pathwayssupporting
confidence: 62%
“…This multifaceted hypothesis may explain why night workers may have a greater risk of developing BC compared to the general population ( 42 , 52 , 55 , 57 ) and why work organisations should implement a strategic procedure to prevent BC. Under these premises and also in light of the new evidence, this review aims to provide an overview of the most relevant risk factors, providing recommendations to fill gaps in risk assessment and suggest novel organisational strategies that occupational physicians should adopt in the workplace, both for the prevention and return-to-work process of female workers affected by BC.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, during the COVID-19 pandemic, trainees are more susceptible to suffering from mood drops because of the sudden work overload in healthcare settings, which are frequently stressful and distinguished by more strenuous shifts, fluctuating work hours, and a high-pressure atmosphere [6]. Moreover, precisely owing to these working conditions, healthcare workers are more likely to report a high prevalence of sleep disturbances with consequential psychological disorders affecting daily activities [7]. Therefore, it is possible to observe a reduction in professional performance among medical staff with severe consequences, such as mistakes due to fatigue leading to adverse clinical outcomes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Though it has been demonstrated that the trend of contagion has differently affected the mental health status of HCWs working in areas with dissimilar incidences of COVID-19 cases [ 23 , 24 ], it is also true that regional differences in stress perception and coping strategies also depend on cultural factors, home/work interface, social support, and economic environment [ 25 , 26 ]. In a Chinese study, comparing subjects coming from Hubei and from non-endemic provinces, health workers in the endemic region showed lower anxiety levels about the COVID-19 epidemic [ 23 ].…”
Section: Introductionmentioning
confidence: 99%